2019
DOI: 10.1108/jadee-03-2018-0038
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of organic tea purchase intentions by Chinese consumers

Abstract: Purpose The purpose of this paper is to examine the factors that influence Chinese consumers’ purchase of organic products, with a focus on organic tea. Design/methodology/approach A structured questionnaire was used to survey 202 shoppers in Guangdong Province, China. The data were analyzed using multivariate regression. Findings The study suggests two significant predictors of organic tea purchase intentions: perceiving organic tea as a healthier alternative to non-organic tea; perceiving the purchase of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 44 publications
4
24
1
9
Order By: Relevance
“…Traditionally, Chinese consumers buy tea products with a main focus on their taste, price, and convenience. However, as income increases and consumption knowledge advances, Chinese consumers pay more attention to the safety and health of tea products [32]. In particular, after COVID-19 pandemic occurs, Chinese consumers prefer organic tea and they are willing to purchase organic tea to replace traditional tea products [3].…”
Section: Product Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, Chinese consumers buy tea products with a main focus on their taste, price, and convenience. However, as income increases and consumption knowledge advances, Chinese consumers pay more attention to the safety and health of tea products [32]. In particular, after COVID-19 pandemic occurs, Chinese consumers prefer organic tea and they are willing to purchase organic tea to replace traditional tea products [3].…”
Section: Product Qualitymentioning
confidence: 99%
“…Traditionally, Chinese consumers do not rely heavily on customer service to purchase tea products because most of tea products are sold through conventional small stores with little or no service [32]. In the last decades, with the emergence of large stores and exclusive stores and the increase in consumers' purchase power, consumers tend to care more about customer service because they have more choices for their money.…”
Section: Customer Servicementioning
confidence: 99%
“…Conventional food remains the highest percentage of global food consumption. Similarly, in Asia, the production and export of organic foods have been increased (James et al , 2019). However, the comparison to domestic consumption remains extremely low (less than 1 per cent of total food consumption) (Rahman et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, interest in organic teas also appears to be gaining momentum. A survey of 202 Chinese shoppers revealed that consumers perceiving organic tea as a healthy option and as a status symbol were more likely to report organic tea purchase intentions (James et al , 2019). Synergistic combinations of herbal teas could also confer health benefits.…”
Section: Discussionmentioning
confidence: 99%